Unpicking the Developmental Relationship Between Oral Language Skills and Reading Comprehension: It's Simple, But Complex. Issue 5 (12th June 2017) - Lervåg, Arne; Hulme, Charles; Melby‐Lervåg, Monica
Abstract : Listening comprehension and word decoding are the two major determinants of the development of reading comprehension. The relative importance of different language skills for the development of listening and reading comprehension remains unclear. In this 5‐year longitudinal study, starting at age 7.5 years ( n  = 198), it was found that the shared variance between vocabulary, grammar, verbal working memory, and inference skills was a powerful longitudinal predictor of variations in both listening and reading comprehension. In line with the simple view of reading, listening comprehension, and word decoding, together with their interaction and curvilinear effects, explains almost all (96%) variation in early reading comprehension skills. Additionally, listening comprehension was a predictor of both the early and later growth of reading comprehension skills.